Sero-epidemiological Study of Toxoplasma gondii among Pregnant Women in Akre City - Shukri Saadi, Hogir Mohammed; Jumaa Ahmed, Ahmed (Kurdistan Journal of Applied Research, 2020)
Recently has been observed globally that toxoplasmosis disease was caused by Toxoplasma gondii and generally its asymptomatic infection in people except pregnant women. Many previous studies were suggested this pathogen transmits by ingesting of undercooked or raw meat contaminated with the oocytes of this parasite. The study aimed to show the seroreactivity of Toxoplasma gondii antibodies among pregnant women and to evaluate association of studied risk factors with infected cases. ELISA technique used for detection of anti-toxoplasma specific IgG and IgM antibodies. A biography form interview for participant was performed to estimate between the risk factors and toxoplasmosis. The present study was carried out from the beginning of October 2018 to the end of March 2019 and included 90 pregnant women visited Akre general hospital. Out of 90 tested samples, 49 (54.46%) and 4 (4.44%) were positive for IgG and IgM respectively. According to residency factor, pregnant women from villages had higher percentages of IgG (57.14%) and IgM (4.08%) than those lived in the city which were recorded 0% and 48.48%of IgM and IgG respectively. A high percentage of IgG (65.64%) and IgM (7.27%) were found among pregnant women with history of miscarriage. Seropositivity for both IgG (61.90 %) and IgM (9.52%) was higher among pregnant women who had cats compared to those without cat. Seroprevalence of IgM and IgG was 9.67% and 54.83% among population who had undercooked meat, while 1.69% and 59.23% were positive for IgM and IgG respectively, in those well cooked meat meal. Highest positive percentage of IgG (77.77%) was recorded at ages 40-50 years while the lowest rate was (40%) at ages <20 year. Through a seropositive reaction was found that age groups as a possible risk factor by ELISA IgG in which risk increased by rising of age categories. Significant correlation was detected between consumption of undercooked meat and cases positive for IgM. It revealed the association between third trimester and cases with positive IgM. In the conclusion, toxoplasmosis is widespread in the area which requires raising awareness among pregnant women to decrease T. gondii infection and subsequently minimize possibilities of congenital transmission.